2001
DOI: 10.1557/proc-692-h9.20.1
|View full text |Cite
|
Sign up to set email alerts
|

Shallow-donor states in spherical quantum dots with parabolic confinement

Abstract: The evidence of a parabolic potential well in quantum wires and dots was reported in the literature, and a parabolic potential is often considered to be a good representation of the "barrier" potential in semiconductor quantum dots. In the present work, the variational and fractionaldimensional space approaches are used in a thorough study of the binding energy of on-center shallow donors in spherical GaAs-GalxAlxAs quantum dots with potential barriers taken either as rectangular [Vb (eV) = 1.247 x for r > R ]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Strictly speaking as 𝑅 → ∞ all these energies should approach zero which is the free particle energy at 𝑘 = 0. Researchers [13,14] have found that the values of binding energies for cubic and spherical quantum dots are very close provided that the dots have similar volumes, which are in good agreement with our results.…”
Section: -1supporting
confidence: 91%
“…Strictly speaking as 𝑅 → ∞ all these energies should approach zero which is the free particle energy at 𝑘 = 0. Researchers [13,14] have found that the values of binding energies for cubic and spherical quantum dots are very close provided that the dots have similar volumes, which are in good agreement with our results.…”
Section: -1supporting
confidence: 91%
“…We have compared the rectangular confinement with other confinements such as spherical and parabolic potentials as done in Ref. [16] in which the effect of diamagnetic susceptibility is not included. We have computed and compared the susceptibility for a hydrogenic donor in a spherical confinement, harmonic oscillator-like and rectangular well-like potentials for a finite QD and observe a strong influence of the shape of confining potential and geometry of the dot on the susceptibility.…”
Section: O Amentioning
confidence: 99%